THE PRODUCTION OF SWEET BREAD SAFE FOR DIABETICS REFERRING TO SNI 01-3840-1995 - Safitri, Pipit (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT Sweet bread for diabetes is whole wheat bread rich in fiber, B vitamins, and phytochemicals. The content of whole wheat flour and corn flour has a lower glycemic index, which helps manage blood sugar levels. The production of sweet bread involves variations of palm sugar in amounts of 10, 20, 30, 40, and 50 grams, as well as variations in whole wheat and corn flour. Testing to ensure the bread is suitable for consumption includes tests for moisture content, ash content, microbial contamination, and organoleptic tests. From the test results, the moisture content in sample 7, using whole wheat flour with 10 grams of palm sugar, was 27.18%, while sample 16, using corn flour with 5 grams of palm sugar, had a moisture content of 28.80%. The best ash content results were found in sample 7 with whole wheat flour and 10 grams of palm sugar, yielding 0.40%, and sample 16 with corn flour and 5 grams of palm sugar, yielding 0.20%. The organoleptic test results were satisfactory, as indicated by blood sugar checks in diabetic patients, and the best microbial contamination test result was scored at 4.Keywords: Bread, Diabetes, Palm Sugar, Whole Wheat Flour, Corn Flour.